2021
DOI: 10.1371/journal.pntd.0008925
|View full text |Cite
|
Sign up to set email alerts
|

Skin maculae, chronic diarrhea, cachexia, and splenomegaly—Late presentation of the first autochthonous case of visceral leishmaniasis in Tanzania

Abstract: A 20-year-old man from Simanjiro district in northern Tanzania presented with a 3-year history of splenomegaly, fatigue, cachexia, skin maculae, and recent onset of watery diarrhea at Kilimanjaro Christian Medical Centre (KCMC) in Northern Tanzania. Due to laboratory findings of pancytopenia, diagnostic workup included bone marrow aspiration cytology and biopsy. Although the rapid test (IT LEISH, rK39 RDT) was negative, blood smear showed amastigote forms of leishmaniasis in macrophages. Repeat bone marrow asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…120 Driven by migration and climate change, recent case reports from Eritrea, Kenya, and Tanzania have demonstrated that the territories in which autochthonous leishmaniases occur are expanding. [121][122][123] Additionally, deforestation and changing patterns of land use for agriculture provide new ecological niches for sandflies. 124,125 Local agriculture, an important source of calories and nutrients for poor communities, is additionally threatened by climate change as rising CO 2 levels contribute to nutrient leaching.…”
Section: Environment Migration Conflict and Climate Change Exacerbate Vulnerability To The Leishmaniasesmentioning
confidence: 99%
“…120 Driven by migration and climate change, recent case reports from Eritrea, Kenya, and Tanzania have demonstrated that the territories in which autochthonous leishmaniases occur are expanding. [121][122][123] Additionally, deforestation and changing patterns of land use for agriculture provide new ecological niches for sandflies. 124,125 Local agriculture, an important source of calories and nutrients for poor communities, is additionally threatened by climate change as rising CO 2 levels contribute to nutrient leaching.…”
Section: Environment Migration Conflict and Climate Change Exacerbate Vulnerability To The Leishmaniasesmentioning
confidence: 99%